2021
DOI: 10.3389/fmicb.2021.744291
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Molecular and Genomic Epidemiology of Morganella morganii in China

Abstract: Objectives: Ongoing acquisition of antimicrobial resistance genes has made Morganella morganii a new clinical treatment challenge. Understanding the molecular epidemiology of M. morganii will contribute to clinical treatment and prevention.Methods: We undertook a 6-year clinical molecular epidemiological investigation of M. morganii from three tertiary hospitals in China since 2014. Antimicrobial susceptibility testing was performed using a VITEK-2 system. All isolates were screened for β-lactam and plasmid-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…Interestingly, all plasmids carrying bla OXA-181 also carry the qnrS1, while plasmids carrying bla NDM-1 often also carry bla SHV-12 . This is consistent with the study by Xiang et al (2021) . IncX3 plasmids can disseminate bla OXA-181 and qnrS via an IS26-flanked composite transposon, or bla NDM and bla SHV-12 via a Tn125-like transposon.…”
Section: Various Antibiotic Resistance Genes Carried By Incx3 Plasmidssupporting
confidence: 94%
“…Interestingly, all plasmids carrying bla OXA-181 also carry the qnrS1, while plasmids carrying bla NDM-1 often also carry bla SHV-12 . This is consistent with the study by Xiang et al (2021) . IncX3 plasmids can disseminate bla OXA-181 and qnrS via an IS26-flanked composite transposon, or bla NDM and bla SHV-12 via a Tn125-like transposon.…”
Section: Various Antibiotic Resistance Genes Carried By Incx3 Plasmidssupporting
confidence: 94%
“…As a result, treatment with quinolones, aminoglycosides, co-trimoxazole, or carbapenems is usually recommended ( 3 6 ). However, the potential for Morganella morganii to acquire other resistance determinants has been increasingly recognized ( 7 ). Recent studies have found extensively resistant strains in sewage samples and among a range of animal sources ( 8 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the MDR region of the AGI1 variant of P. mirabilis PmBR607, the class 1 integron was followed by an ISCR1 element and the bla CTXM–2 ESBL gene. The MDR region of the recently described PGI2 variant of M. morganii zy_m28 ( Xiang et al, 2021 ) contained numerous copies of IS 26 elements and antibiotic resistance genes (ARGs), including the bla CTX–M–3 ESBL gene, the fosfomycin resistance gene fosA3 , and the fluoroquinolone acetylating aminoglycoside-(6′)- N -acetyltransferase gene aac (6′)-Ib-cr, as already described in PGI2-C55 ( Lei et al, 2020b ).…”
Section: Resultsmentioning
confidence: 66%